Music accompaniment in Kun Seng Keng Lion dance during Genting World Lion Dance Championship from 1994-2018 / Lim Hong Zhi - Lim , Hong Zhi (2021)
Lion Dance is a diasporic Chinese tradition and a typical performing arts genre in Malaysia. Mostly with the goal of promoting lion dance, Malaysia has been the first to organise the Genting World Lion Dance Championship biannually by the Genting Group and Selangor Dragon and Lion Dance Federation since 1994 in Arena Star, Genting, Malaysia. Competition has altered the context of street lion dance performances, and there is inadequate of research on modern re-contextualised lion dance in previous works of literature, including new elements applied to its performance and music. Therefore, this study addresses the literature gap by choosing the Kun Seng Keng Lion Dance and Dragon Association in Malaysia as its subject for research and analysed changes to accompanying traditional lion dance music within the framework of the competition. The Kun Seng Keng Lion Dance and Dragon Association established an international reputation with twelve champions in the past thirteen World Genting Lion Dance Championships from 1994 to 2018 and won the East Lion King title. Video analysis, performance analysis, transcription, analysis of the score, semi-structured interviews and observation are the approaches used during this study. The results of this study reveal a discussion about cultural changes and musical significance in the context of recontextualised lion dance competitions.